QISAH AL-MI’RAJ DALAM NASKAH PERPUSTAKAAN MASJID AGUNG SURAKARTA DAN PERPUSTAKAAN NASIONAL REPUBLIK INDONESIA (Kajian Filologi Arab) - Roro Fatikhin (LPPM Universitas KH. A. Wahab Hasbullah, 2018)
Everything that people thought in the past often different from those that existed at the time now. Besides thought inherited by the characters in the past is an inherited form of very known. but often valuable for such thinking can only be found on the heritage in the form of manuscripts alone, like one Arabic manuscripts found in the Library of the Great Mosque of Surakarta containing about the journey Isra' mi'raj Prophet Muhammad. This paper is a study Philology research that makes the ancient manuscripts in Arabic as an object of study by using landasan methode in doing redaction. Research stage of philological studies conducted by the author of this entry in category library research (library research) that the author tries to find the data that is sustainable with the object of this study philology. By using analytical theory structuralism Robert Stanton, this object will be studied further to find out more in the intrinsic elements that exist in the script of the story in order to make meaning is found in the story from beginning to end more comprehensively. From research, the author is able to save an Arabic codex which became the object of study in this paper, the manuscript which contains the story of the journey of the Prophet Muhammad, sometimes referred to term isra’ mi’raj. By using the theory of structuralism Robert Stanton, the author express something which is in the original text by explaining abaut substances that happened in the story. The substances are topic, the fact of story, and the medium of story. Key words: Manuscript, Script, Philology, Isra’ Mi’raj.